Comparison of clinical efficacy between tibial cortex transverse transport and platelet-rich plasma treatment for severe diabetic foot ulcers - Zhen, Pu-Xiang; Su, Hong-Jie; Yang, Si-Jie; Chen, Xiang; Lin, Zhan-Ming; Liu, Sai-Nan (Frontiers in Surgery, 2025)
ObjectiveThis study aims to compare the effects of tibial cortex transverse transport (TTT) and platelet-rich plasma (PRP) on the healing of severe diabetic foot ulcers, evaluate the clinical efficacy of TTT, and explore its potential impact on lower limb circulation.MethodsA retrospective analysis was conducted on two patient groups treated at our hospital between July 2019 and June 2022. One group underwent TTT, while the other received PRP therapy. Both groups had Wagner level 3 or higher ulcers. An 18-month follow-up was performed for both groups, during which we documented wound healing progress and healing times to assess clinical efficacy. To investigate lower limb blood flow recovery, lower limb arterial ultrasound was used to measure blood flow velocities in the affected popliteal and dorsalis pedis arteries. Additionally, ELISA was employed to measure the stromal cell-derived factor-1 (SDF-1) levels of angiogenic factors in peripheral blood.ResultsA total of 60 diabetic foot ulcers (DFUs) patients were enrolled in our study, with 30 patients in each group: TTT-treated and PRP-treated. During the 18-month follow-up, the wound healing rate in the TTT-treated group was significantly higher than in the PRP-treated group [96.67% (29/30) vs. 80% (24/30), p < 0.05]. Furthermore, the healing time in the TTT-treated group was shorter (3.02 ± 0.84 vs. 6.04 ± 0.85 months, p < 0.001). The amputation rate [3.33% (1/30) vs. 20% (6/30), p < 0.05] and recurrence rate [6.67% (2/30) vs. 26.67% (8/30), p < 0.05] in the TTT-treated group were lower than those in the PRP-treated group. After 1 month and 18 months of treatment, the flow velocities in the popliteal artery (68.93 ± 2.69 vs. 58.14 ± 2.48 cm/s, p < 0.001; 55.68 ± 3.43 vs. 46.07 ± 3.02 cm/s, p < 0.001) and dorsalis pedis artery (46.45 ± 2.77 vs. 36.46 ± 2.83 cm/s, p < 0.001; 38.63 ± 2.40 vs. 29.82 ± 2.15 cm/s, p < 0.001) in the TTT-treated group were significantly higher than in the PRP-treated group. Additionally, the TTT-treated group showed higher levels of SDF-1 expression (375.36 ± 13.52 vs. 251.93 ± 9.82 pg/ml, p < 0.001; 256.62 ± 13.19 vs. 239.96 ± 10.78 pg/ml, p < 0.001).ConclusionOur results suggest that TTT treatment is more clinically effective than PRP for treating severe DFUs. This increased efficacy may be attributed to enhanced lower limb blood flow, which is potentially driven by elevated SDF-1 levels.